Abundance and Diversity of Plankton as Bioindicators of Coastal Paddy-Field Water Quality in Batang Regency, Indonesia - Ari Handriatni; Heri Ariadi; Farchan Mushaf Al Ramadhani; Ubad Badrudin; Syakiroh Jazilah; Rohmatul Amin; M. Akmal Faza; Samsul Ma'Arif; Candra Dwi Pradana; Anandya Hadiprasetya (Postgraduate, University of Mataram, 2025)
This investigation evaluated spatial and temporal variations in plankton abundance and community structure to determine their effectiveness as bioindicators of water quality in coastal rice-field ecosystems of Batang Regency, Central Java. Plankton samples were collected from five sampling stations using 80 mL film vials and subsequently identified through laboratory-based taxonomic analysis. Key physicochemical factors were measured ex situ, and the analyses evaluated plankton abundance, Shannon–Wiener diversity index (H’), evenness (e), dominance (C), and saprobic index. Results demonstrated relatively low plankton abundance, with Bacillariophyceae (40%), particularly Chaetoceros sp., representing the principal taxonomic group, followed by Chlorella sp. Moderate diversity levels (H’ = 1.45–2.85), high evenness (e > 0.6), and low dominance (C < 0.5) indicated a community structure with stable ecological dynamics. Most water quality parameters conformed to Indonesian water-quality criteria, characterized by a salinity of 0.5 g/L, temperatures of 23–24 °C, and dissolved-oxygen concentrations above 4.0 mg/L. However, the saprobic index revealed light to moderate pollution at stations near settlements and downstream river segments, likely influenced by domestic wastewater, agricultural runoff, and seawater intrusion. Overall, the ecosystem remained supportive of primary productivity, emphasizing the significance of plankton as sensitive indicators for monitoring coastal agricultural environments